Green IT indicator – GrIT / Dr. Erne Suzila Kassim, Hanitahaiza Hairudin and Sri Fatiany Abdul Kader Jailani - Kassim, Dr. Erne Suzila; Hairudin, Hanitahaiza; Abdul Kader Jailani, Sri Fatiany (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
As environmental sustainability has become one of the world's concerns, we develop an indicator to measure the level of green IT maturity in organization, known as GrIT. Green IT is an important practice since it consists of activities that minimize the negative impact of IT use on the environment. Based on previous empirical findings, we categorize attitude, policy, practice, technology, governance and motivation as green IT indicator dimensions. GrIT is able to show how mature green IT is practiced, which particular dimension is having the highest and lowest score, what can be done to promote for better green IT and the timeline of green IT performance.